2018
DOI: 10.1253/circj.cj-17-1092
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes and Predictors of Target Lesion Revascularization for Non-Left Main Coronary Bifurcation Lesions Following Two-Stent Strategy With 2nd-Generation Drug-Eluting Stents

Abstract: the 2-stent strategy using 2nd-generation DES for non-left main coronary bifurcation lesions. Methods Study Sample and ProtocolThe study sample retrospectively included 356 consecutive patients with 364 non-left main coronary bifurcation lesions treated with the 2-stent strategy using 2nd-generation DES between 2010 and 2014. Clinical follow-up was censored by death and loss to follow-up. A 2-year clinical follow-up was achieved in 353 patients (99.2%). Angiographic followup was scheduled 8 and 20 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 33 Previous studies have shown that the cumulative incidence of MACE in bifurcated coronary artery lesions is higher than that in non-bifurcated coronary artery lesions, especially in patients treated with a dual stent strategy. 34 In severe calcification, stent insufficiency is common and may increase the risk of restenosis and stent thrombosis. 35 In addition, severe calcification lesions increase the difficulty of stent delivery.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Previous studies have shown that the cumulative incidence of MACE in bifurcated coronary artery lesions is higher than that in non-bifurcated coronary artery lesions, especially in patients treated with a dual stent strategy. 34 In severe calcification, stent insufficiency is common and may increase the risk of restenosis and stent thrombosis. 35 In addition, severe calcification lesions increase the difficulty of stent delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In Korean registries, crush stenting was most frequently used in 41–53% and culotte stenting was less used in 2–12% [ 4 , 18 ]. On the contrary, there was higher prevalence of culotte stenting in Japan (16–81%) [ 14 , 19 ]. After introducing new-generation DES, TLR was dramatically reduced in Korea (16.1–7.8%) [ 17 ] and Japan (13.6–6.7%) [ 14 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there was higher prevalence of culotte stenting in Japan (16–81%) [ 14 , 19 ]. After introducing new-generation DES, TLR was dramatically reduced in Korea (16.1–7.8%) [ 17 ] and Japan (13.6–6.7%) [ 14 , 19 ]. Culotte stenting provides a certain DES coverage in the whole bifurcation with less layer; however, there are risks of MV or SB occlusion during the procedure as well as inadequate expansion of branch ostium due to jailed strut [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-eluting stents have shown superiority over bare metal stents, but there are still unmet needs in this scenario. 8,15 Late outcomes still need to improve and, in this aspect, there are some treatment strategies that depend on the individual characteristics of each patient and aim to reduce the occurrence of late MACE. 16,17 The most used techniques for PCI in bifurcation lesions are provisional stenting, culotte, mini-crush, step-crush, DK crush, T-stenting, TAP, V-stenting, and simultaneous kissing stents.…”
Section: Journal Of Transcatheter Interventionsmentioning
confidence: 99%